Breaking with the spatial-cycle model: the shift towards 'syncurbanization' in polycentric urban regions. Issue 1 (2nd January 2022) - Humer, Alois; Cardoso, Rodrigo; Meijers, Evert
ABSTRACT: This paper criticizes traditional models of urban–regional expansion, which depart from monocentric ideals of urban core and ring. The original spatial-cycle model (SCM) suggests repeating stages of urbanization, suburbanization, disurbanization and re-urbanization. We reconceptualize the relations between core(s) and ring(s) to test the formation of urban regions under mono-, multi- and polycentric trajectories. The analysis employs local population data in functional urban regions in Finland, Austria and the Netherlands, three countries with different urbanization patterns, for the period 1961–2011. Results suggest a 'break of the cycle' in polycentric regions and a shift towards a different period, which we call 'syncurbanization'.